2021
DOI: 10.5957/jst/2021.6.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Fidelity Surrogate Models for VPP Aerodynamic Input Data

Abstract: Predicting the performance of a sail design is important for optimising the performance of a yacht, and Velocity Prediction Programs (VPPs) are commonly used for this purpose. The aerodynamic force data for a VPP is often calculated using Computational Fluid Dynamics (CFD) models, but these can be computationally expensive. A full VPP analysis for sail design is therefore usually restricted to high-budget design projects or research activities and is not practical for many industry projects. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…These can be used to improve the accuracy of the surrogate model, or to allow the use of fewer high-fidelity points for the same model accuracy. Further details on kriging and multi-fidelity kriging can be found in Forrester et al (2007; and Peart et al (2021).…”
Section: Multi-fidelity Krigingmentioning
confidence: 99%
See 3 more Smart Citations
“…These can be used to improve the accuracy of the surrogate model, or to allow the use of fewer high-fidelity points for the same model accuracy. Further details on kriging and multi-fidelity kriging can be found in Forrester et al (2007; and Peart et al (2021).…”
Section: Multi-fidelity Krigingmentioning
confidence: 99%
“…This results in fewer high-fidelity points being needed. The difference in fidelity can be as a result of having different mesh resolutions (Serani et al, 2019), different solvers (Pellegrini et al, 2016), different models of the physics (Sacher et al, 2021), a combination of experimental and numerical methods (Kuya et al, 2012), or using data points from previous simulations of similar designs (Peart et al, 2021). Multifidelity methods have the potential to further reduce the computational cost of evaluating a function, or improve the accuracy for the same computational cost, when compared to conventional surrogate modelling methods (de Baar and Roberts, 2015;Peart et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of numerical data can be expensive due to the cost of computations. In (Peart, et al, 2021) several approaches to reduce the calculation requirements are suggested. In (Cella, et al, 2016) it is possible to find an example on how sail trim optimization procedures and analytical VPPs can be coupled.…”
Section: Foils Design Problem Descriptionmentioning
confidence: 99%